Pengaruh Citra Merek dan Ulasan Customer Online terhadap Minat Pembelian Ulang pada Produk Viva Cosmetic di Aplikasi Shopee (Studi Pada Konsumen Viva Cosmetic di Kota Malang) - Rohmah, Yaumi; Zagladi, Arif Noviarakhman (IPM2KPE, 2025)
This study aims to analyze the influence of brand image and online customer reviews on repurchase intention of Viva cosmetic products in Malang City. The method used in this study is a quantitative method with a purposive sampling technique. Respondents in this study were consumers who live in Malang City, have a Shopee account, and have purchased and used Viva cosmetic products at least twice. The research sample consisted of 73 people determined using Calculator.net. Data were collected through an online questionnaire and analyzed using the Partial Least Squares (PLS) method. The results showed that all variable indicators had a loading factor value > 0.5, so they could be declared valid. The validity test using Average Variance Extracted (AVE) showed a value of more than 0.50 for all variables, with the highest value in the online customer review variable (0.717). Reliability tests with Composite Reliability and Cronbach's Alpha showed that all variables had values ​​above 0.7, indicating high reliability. The R Square analysis showed that the brand image and online customer reviews variables influenced repurchase intention by 69%. The path coefficient results show that brand image has a significant effect on repurchase intention with a T-statistic value of 7.206 (>1.96) and a p-value of 0.000 (<0.05). Online customer reviews also have a significant effect on repurchase intention with a T-statistic value of 2.096 (>1.96) and a p-value of 0.037 (<0.05). In conclusion, brand image and online customer reviews have a positive and significant effect on repurchase intention of Viva cosmetic products. The better the brand image in the eyes of consumers and the more positive the reviews received, the higher the likelihood of consumers to make repeat purchases. Keywords: Brand Image, Online Customer Reviews, Repurchase Intention